Artistic understanding of peasant life in proverbs - Turaeva Laylo Omonovna (Genius Journals, 2022)
It is noted that the religious views and landscapes associated with the life of the peasants are artistically expressed in folk proverbs in a peculiar way. In particular, the multi-volume “Uzbek folk proverbc” in the “Uzbek folk art” series contains more than a hundred articles on agriculture, wich glorify the devotion and love of the faemer to his work, his diligence, aspiration and determination. This article describes the interpretation of Uzbek folk proverbs related to the life of dekhkans
Keywords: Proverbs; economy; religious; ideas